Solvent Extraction of Metal Ions from Synthetic Copper Leaching Solution Using r4ncy - Navarro-Donoso, P; Vargas-Riquelme, C (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Recent works suggest that the use of ionic liquids in the copper solvent extraction industry is feasible. However, the reports did not use real solutions (or synthetic solutions with various elements). This fact remains poorly established, and the interaction efficiencies are still under study. The objective of this research is to explore the extraction and stripping of the four major elements present in a copper industrial pregnant leach solution (Cu(II), Fe(III), Mn(II), and Zn(II)) using the methyltrioctyl/decylammonium bis(2,4,4-trimethylpentyl)phosphinate (R4NCy) ionic liquid as an extractant. The work conditions studied in extraction were ionic liquid concentration, initial pH, and O/A ratio, and in stripping were H2SO4 concentration and O/A ratio. The test was carried out at room temperature and ambient pressure. High efficiency and selectivity (99.82% and 113,755 over Cu(II), respectively) were observed for Fe(III) extraction over the other elements. Moreover, after the extraction test, significant difficulty in stripping Fe(III) loaded in the ionic liquid was observed (28.7% at 0.5 M of H2SO4). Finally, the present study demonstrates that the R4NCy ionic liquid is not suitable for copper extraction because it has a higher selectivity for Fe(III) and Zn(II). © 2022 by the authors. Licensee MDPI, Basel, Switzerland.